2017
DOI: 10.1016/j.ultsonch.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the pitting of potato starch granules during high frequency ultrasound treatment

Abstract: In this paper, the pitting of potato starch granules in aqueous suspensions (1%) by high-frequency high-power ultrasound (850kHz at a power of 0.2W, 2W or 3.7W; and also 500kHz and 1MHz at a power of 2W) is reported. The number of pits per starch granules was found to be independent of the amylose content of starches, and the surface properties of starch granules as modified through SDS and ethanol washing. At 850kHz, the maximum number of pits per starch granule, for both normal and waxy starches, did not exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…No clear change using polarized light pattern was observed, which also included the maltese cross, when ultrasound was used even at higher amplitude (70%) and time (15 min). Bai et al also observed that maltese cross on the starch granules was preserved after ultrasonic treatment, as the pits depth were not deep enough to affect the crystalline regions of the starch granules. It was an indication that ultrasound may have disrupted the amorphous regions of the starch structure, in these experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…No clear change using polarized light pattern was observed, which also included the maltese cross, when ultrasound was used even at higher amplitude (70%) and time (15 min). Bai et al also observed that maltese cross on the starch granules was preserved after ultrasonic treatment, as the pits depth were not deep enough to affect the crystalline regions of the starch granules. It was an indication that ultrasound may have disrupted the amorphous regions of the starch structure, in these experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Starch with larger granule size (e.g., potato starch) was found to be more intensely affected by ultrasound treatment, and the extent of erosion was found to increase with longer treatment time (Carmona-García et al, 2016). In addition, more severe granule breaks were observed in areas close to the Maltese cross, corresponding to its fragile surface (Bai et al, 2017;Carmona-García et al, 2016). Degrois et al (1974) and Gallant et al (1972) examined the effects of surrounding gases (e.g., air, hydrogen, oxygen, and carbon dioxide) on the erosion of starch granules during ultrasound treatment.…”
Section: Starch Morphologymentioning
confidence: 99%
“…Majzoobi et al revealed that cross‐linked wheat starch was more resilient to ultrasound changes than its native counterpart. Bai et al reported that the number of pit induced by ultrasound was independent of amylose content and surface morphology, although the granule size had a positive effect. Miano et al concluded that ultrasound technology can reduce the hydration time of corn kernels without affecting their starch properties.…”
Section: Introductionmentioning
confidence: 99%